Using Transmission Line Matrix Method for Metamaterial Structures Simulation - Abd El-Azeem, Mohamed Hassan (Journal of Advanced Vehicle System, 2017)
Split Ring Resonators (SRRs) are widely used to design metamaterial structures. These structures when excited by suitable electromagnetic fields have resonance behavior and show unusual properties near the resonance frequency region. In this paper, Transmission Line Matrix Method (TLM) is used as a new, efficient and accurate time domain method using the 3D Symmetrical Condensed Node (SCN) to study, design and simulate SRRs as a metamaterial structure. This approach is done by using a modified written FORTRAN code. Results of TLM verified with those obtained by measured data of the fabricated structure and comparison showed great matching between results.